Using Pulse 2 to Teach and Assess Malaysian Pupils Speaking Skill - Goh, Ying Tong; Aziz, Azlina Abdul (International Journal of Publication and Social Studies, 2020)
Textbook plays an important role in ESL class worldwide due to its convenience of providing ready-made language activities. In Malaysian ESL class, locally produced English textbooks have always been the core teaching and learning material but in the new CEFR-aligned curriculum, Pulse 2, a foreign English textbook was introduced to the local secondary school ESL class. Hence, the use of Pulse 2 in teaching and assessing the pupils’ language skills is still considered new to many teachers and its practicality in the local ESL class is yet to be discovered. This study attempts to explore the secondary school teachers’ perception on the speaking activities in this foreign English textbook to teach and assess their pupils’ speaking skill particularly. Survey was employed for teachers to rate the practicality of various aspects of the speaking activities. The overall findings indicated that the speaking activities were mainly rated practical to be used to teach speaking skill and easy to be utilised for speaking assessment purpose. In conclusion, it is evident that the speaking activities in Pulse 2 are widely considered useful in assisting the local teachers in the local ESL classes despite being authored by foreign textbook writer.